What Do Labour Economics and Industrial Relations Have to Say to Each Other? - GUNDERSON, Morley (Industrial Relations / Relations Industrielles, 2023)
Mutual gains can be made through greater cross-pollination between labour economics and industrial relations. The paper is organized around common criticisms of labour economics, with examples from industrial relations. Such criticisms, and their underlying principles, often explain important concepts in industrial relations, which can provide insights that may enhance labour economics. The intent here is to apply a forward-looking lens to advance theoretical and empirical reflection on current and future aspects of work and employment.